Role of herbal interventions in diabetes management - Omkar Kulkarni; Priya Khare; Anuj Agrawal; Gayatri Ganu (International Journal of Pharma and Bio Sciences, 2020)
Diabetes mellitus is becoming a common metabolic disorder which has a serious threat to public health worldwide. Though much vigorous research is being undertaken in modern research, it is very challenging to manage diabetes and avoid complications with better quality of life. By conducting a large number of research work, numerous traditional medicines have been researched for diabetes. It is observed that the current allopathic treatment leads to numerous side effects and complications amongst the diabetic population. Thus, a new way out to avoid such complications is to adopt herbal remedies for the management of diabetes. Phytoconstituents and extracts isolated from different natural resources especially plants have always been a rich arsenal for controlling and treating diabetes and its complications. So this review helps the reader to understand the diabetes pathophysiology, possible ways in which polyherbal formulations can help management of diabetes mellitus.